Modelling of 3D solar module based on flexible photovoltaic panels - Mazur, Marek; Józwik, Michał; Malowany, Krzysztof; Szeląg, Łukasz (Photonics Letters of Poland, 2022)
This paper presents a new concept of a photovoltaic module. The increase in efficiency is obtained by using a three-dimensional form of flexible photovoltaic panels with an additional reflecting mirror. A flexible panel is distributed over the entire inner surface of the cylinder, while the mirror distributes the flux on its surface. The comparison of selected solutions for a mirror shape is realized with numerical simulations. The irradiance results for absorbed flux are discussed on the ground of possible improvements. Full Text: PDF References M.Y. Levy, "Maturity of Photovoltaic Solar-Energy Conversion" (InTech 2011). CrossRef L. M. Fraas, L.D. Partain, "Solar Cells and Their Applications" (Wiley 2010). CrossRef X. Li, P. Li, Z. Wu, D. Luo, H-Y. Yu, Z-H. Lu, "Review and perspective of materials for flexible solar cells", Materials Reports: Energy, 1 (2021). CrossRef N. Gakkhar, M.K. Soni, and S. Jakhar, "Experimental and Theoretical Analysis of Hybrid Concentrated Photovoltaic/thermal System Using Parabolic Trough Collector", Appl. Therm. Eng. 171, 115069 (2020). CrossRef V. Kumar, R.L. Shrivastava, S.P. Untawale, Fresnel lens: "A promising alternative of reflectors in concentrated solar power", Renew. Sust. Energ. Rev. 44 (2015). CrossRef https://lambdares.com/tracepro/ DirectLink